Synthesis, evaluation of drug delivery potential, and the quantum chemical investigation on a molecular imprinted polymer for quetiapine antipsychotic; a joint experimental and density functional theory study - Hoseini chehreghani, Seyyedeh Fatemeh; Aberoomand Azar, Parviz; Shekarchi, Maryam; Daraei, Bahram (Frontiers in Chemistry, 2022)
In this project, the quetiapine drug was used as the template for synthesis of a molecular imprinted polymer (MIP). The polymerization approach for preparation of this composite was precipitation, where methacrylic acid (MAA), ethylene glycol dimethacrylate (EGDMA), and 2,2-azobisissobutyronitrile (AIBN) were used as the functional monomer, the cross-linker, and the initiator, respectively. Scanning electron microscopy (SEM) showed that the diameter of the nanoparticles is about 70 nm. The adsorption rates of quetiapine to the MIP host were evaluated at different pHs, and the results showed that the highest adsorption values were obtained at pH = 7. Moreover, the kinetics of the adsorption process was detected to follow the Langmuir isotherm (R2 = 0.9926) and the pseudo-second-order kinetics (R2 = 0.9937). The results confirmed the high capability of the synthesized MIPs as pharmaceutical carriers for quetiapine. Furthermore, the kinetics of the drug release from the MIP follows the Higuchi model at the pHs of 5.8–6.8 and the Korsmeyer–Peppas model at the pHs of 1.2–5. Finally, in light of the density functional theory (DFT)-based quantum chemical descriptors, the polymer–quetiapine drug complex was designed and investigated. The results showed that there is a strong interaction between the host (polymer) and the guest (drug) due to several hydrogen bonds and other intermolecular (polar) interactions.